NEW DISTRIBUTIONAL RECORD OF POMADASYS JUBELINI (CUVIER) ALONG THE INDIAN COAST - Dorairaj, K (Indian Journal of Fisheries, 2011)
Pomadasys jubelini (Cuvier) has been recorded for the first time from the Indian coast based on a specimen obtained from the Bombay coast. A description of the species has been given.